Harnessed to the Pole : Sledge Dogs in Service to American Explorers of the Arctic 1853-1909 - Nickerson, Sheila B. (Book collections on Project MUSE., 2014)
In the second half of the nineteenth century, an epic race was underway in some of the most brutal stretches on the planet. Explorers from around the world hoped to stake their claim on the Arctic, with the North Pole being the ultimate prize. Those with the greatest success found that the fastest way to travel was on four legs-using a team of hardworking sledge dogs. Harnessed to the Pole follows the adventures of eight American explorers and their dog teams, starting with Elisha Kent Kane and ending with Robert Peary, controversial claimant of the title of first to reach the North Pole. While history has long forgotten these "little camels of the north," Sheila Nickerson reveals how critical dogs were to the Arctic conquest. Besides providing transportation in extreme conditions, sledge dogs protected against wolves and polar bears, helped in hunting, found their way through storms, and provided warmth in extreme cold. They also faced rough handling, starvation, and the possibility of being left behind as expeditions plunged ahead. Harnessed to the Pole is an extraordinary-and unflinching-look at the dogs that raced to the top of the world